2019
DOI: 10.1038/s41598-019-47442-8
|View full text |Cite
|
Sign up to set email alerts
|

Neonicotinoid seed treatments of soybean provide negligible benefits to US farmers

Abstract: Neonicotinoids are the most widely used insecticides worldwide and are typically deployed as seed treatments (hereafter NST) in many grain and oilseed crops, including soybeans. However, there is a surprising dearth of information regarding NST effectiveness in increasing soybean seed yield, and most published data suggest weak, or inconsistent yield benefit. The US is the key soybean-producing nation worldwide and this work includes soybean yield data from 194 randomized and replicated field studies conducted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
50
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 71 publications
(55 citation statements)
references
References 26 publications
3
50
1
Order By: Relevance
“…For example, Wilde et al [61] evaluated the effect of seed treatments on wireworms in corn and found that this approach increased plant stands and grain yield almost 50% of the time, mainly when insects were present in high numbers. The same conclusion emerged from an overall analysis of soybean yield increases across the USA [51,56], in which insecticide seed treatment was found to be useful only when three foliar-feeding pest species were present at the beginning of the summer. Cox and Cherney [48] showed, however, that there is high variability in soybean yield for the same varieties and seed densities at different locations in North America, and that the use of insecticide seed treatments did not provide benefits to all growers.…”
Section: Effects Of Neonicotinoids On Corn and Soybean Yieldsmentioning
confidence: 60%
See 1 more Smart Citation
“…For example, Wilde et al [61] evaluated the effect of seed treatments on wireworms in corn and found that this approach increased plant stands and grain yield almost 50% of the time, mainly when insects were present in high numbers. The same conclusion emerged from an overall analysis of soybean yield increases across the USA [51,56], in which insecticide seed treatment was found to be useful only when three foliar-feeding pest species were present at the beginning of the summer. Cox and Cherney [48] showed, however, that there is high variability in soybean yield for the same varieties and seed densities at different locations in North America, and that the use of insecticide seed treatments did not provide benefits to all growers.…”
Section: Effects Of Neonicotinoids On Corn and Soybean Yieldsmentioning
confidence: 60%
“…The debate surrounding the prophylactic use of neonicotinoids has mainly focused on the potential yield increase in corn and soybeans. Recent studies have sought to analyze whether yield differences can be observed in soybean with or without neonicotinoid seed treatments targeting soybean aphids, Aphis glycines Matsumura [46,47,48,49,50,51,52,53,54,55,56]. A few studies demonstrated yield increases with the use of neonicotinoid treated seeds, mainly when more than one type of pest was present in the field [51,52], while other studies presented no differences.…”
Section: Introductionmentioning
confidence: 99%
“…For similar reasons, our findings on insecticide use trends for counties in California should be interpreted cautiously given the lack of seed treatment data in that state. Similarly, our results point to a need for more detailed investigation of the combined agronomic and socioeconomic drivers of neonicotinoid seed treatments, which do not seem to be cleanly related to pest pressure or field-level economics 24,30,37,38 .…”
Section: Discussionmentioning
confidence: 71%
“…Prophylactic applications of foliar insecticide and fungicide are not recommended as they are generally not associated with an economic benefit (Bluck, Lindsey, Dorrance, & Metzger, 2015; Mourtzinis, Marburger, Gaska, & Conley, 2016; Ng, Lindsey, Michel, & Dorrance, 2018). Similarly, prophylactic use of fungicide‐ and/or insecticide‐treated seed does not provide a consistent economic benefit for different combinations of consequential management practices, such as seeding rate (Mourtzinis et al., 2019a). Market prices and pest pressure both play an important role in determining where insecticide and fungicide applications are likely to be profitable (Gaspar et al., 2015).…”
Section: Discussionmentioning
confidence: 99%